AN INVESTIGATION INTO THE STRUCTURAL AND SEMANTIC FEATURES OF SENTENCE TYPES IN ENGLISH AND VIETNAMESE DETERGENT PRODUCT ADVERTISEMENTS DISCOURSE - Tăng Thị Thanh Thảo (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aimed at conducting an investigation on structural and semantic features of sentence types in English and Vietnamese detergent advertisements. Therefore, it analyzed, compared and contrasted the differences and similarities in detergent products advertisements in English and Vietnamese in terms of structural and semantic features. The data for analysis in this thesis were 200 samples of advertisement for detergent products advertisements in the the UK and in Vietnam. Regarding structural features, this thesis focused on simple, complex, compound, compound-complex and inverterted sentence as well. For semactic features, four types were examined: declarative, imperative, interrogative and exclamatory sentence. With each area, this thesis analysed EDPAs and VDPAs and then found out the similarities as well as differences in both languages. Based on the findings, the thesis gave out some implications and suggestions for teaching and learning in both languages. It is hoped that the result of the thesis is a useful reference to those who are interested in sentence types used in detergent product advertisements. As a result, producers can use types of sentence to make their products more attractive and customers will understand more about the products so that they can have the most suitable choice.